Dor nas costas: prevalência e fatores associados em comunidades quilombolas da Bahia - Luis Rogerio Cosme Silva Santos (2014)
Introduction: Back pain (BP) is viewed as one of the major health problems in Brazil. An estimated 60 to 80 percent of the world population is likely to suffer either from acute or subacute back pain throughout life. Occupational, sociocultural and behavioural factors cause high prevalence of BP in different populations. In addition, back pain adversely affects the routine of such individuals, leading to cause whether temporary or permanent incapability of working and other daily life activities. Thus, it has been viewed as one of the major reasons for labour abseenteism, increasing the social security and health system costs. With regard to remaining quilombola individuals, general living conditions, affected by poverty, low education level, as well as iniquities in the field of health, represent a scenario of socioeconomic vulnerability. These burden on their condition of being black, and outline a health profile, characterized by higher rates of mortality, social violence, hunger, occupational hazards, low access to health services, and high prevalence of chronic diseases, among which, BP. Objective: to describe the prevalence and investigate the factors associated with back pain in adults who live in quilombola territories in Vitória da Conquista (Bahia). Method: a population-based inquiry with data from COMQUISTA project was conducted in 25 quilombola communities from Vitória da Conquista, Bahia, based on 5 randomly selected municipalities, in 2011, so as to evaluate both the health and its determinants. The sampling universe involved 2.935 individuals. The sampling (n=750) was done by selecting homes through sortition. Due to the heterogeneous feature of the events investigated in the matrix project (COMQUISTA), a prevalence of 50 percent (5 percent of precision and confidence interval of 95 percent - IC95%) was estimated in the inquiry. Semi-structured interviews were carried out to investigate socio-demographic and occupational characteristics, life habits, and health conditions: gender, age, marital status, education, colour, income, employment situation, tobaccoism, Body Mass Index (BMI), physical activity. Associations between the explanatory variables and the outcome (Prevalence Ratio - PR) were calculated through Poisson regression, with an estimation of robust variable according to the hierarchical data entry. Results: The prevalence of BP was 39,3%. In the multivariable analysis, group ages from 31 to 50 (RP 1,47; IC95% 1,12-1,94) and over 50 (RP 1,80; IC95% 1,38-2,35) were associated with the outcome (p 0,01). Significant association between smoking and BP (RP 1,31; IC95% 1,08-1,59) was viewed in the final model (p 0,01). The employment relationship was not associated. Conclusions: The inquiry indicated high prevalence of BP in socially vulnerable quilombola adults from rural area. Due to the cross-sectional design, cause and effect cannot be determined. However, the results were evocative concerning the possible connection between individual factors (age) and life habits (tobaccoism) and BP. Further studies are still required to enlighten the connections between employment, working conditions, and self-report of back pain. Results indicate the necessity for the development of prevention strategies, which aim at controlling and reducing the prevalence of BP in the quilombola communities. Intersectoral activities are favored so as to provide quilombola adults with healthy habits and also access to care, diagnosis, and treatment of vertebral column problems.